Honokiol and Magnolol: Insights into Their Antidermatophytic Effects - Adriana Trifan (MDPI AG, 2021)
Dermatophyte infections represent a significant public health concern, with an alarming negative impact caused by unsuccessful therapeutic regimens. Natural products have been highlighted as a promising alternative, due to their long-standing traditional use and increasing scientific recognition. In this study, honokiol and magnolol, the main bioactives from Magnolia spp. bark, were investigated for their antidermatophytic activity. The antifungal screening was performed using dermatophyte standard strains and clinical isolates. The minimal inhibitory concentration (MIC) and the minimal fungicidal concentration (MFC) were determined in accordance with EUCAST-AFST guidelines, with minor modifications. The effects on ergosterol biosynthesis were assessed in Trichophyton rubrum cells by HPLC-DAD. Putative interactions with terbinafine against T. rubrum were evaluated by the checkerboard method. Their impact on cells’ viability and pro-inflammatory cytokines (IL-1β, IL-8 and TNF-α) was shown using an ex vivo human neutrophils model. Honokiol and magnolol were highly active against tested dermatophytes, with MIC and MFC values of 8 and 16 mg/L, respectively. The mechanism of action involved the inhibition of ergosterol biosynthesis, with accumulation of squalene in T. rubrum cells. Synergy was assessed for binary mixtures of magnolol with terbinafine (FICI = 0.50), while honokiol-terbinafine combinations displayed only additive effects (FICI = 0.56). In addition, magnolol displayed inhibitory effects towards IL-1β, IL-8 and TNF-α released from lipopolysaccharide (LPS)-stimulated human neutrophils, while honokiol only decreased IL-1β secretion, compared to the untreated control. Overall, honokiol and magnolol acted as fungicidal agents against dermatophytes, with impairment of ergosterol biosynthesis.